On properties of the solutions of the Weber equation - Trukhan, Yu.S. (Carpathian Mathematical Publications, 2015)
Growth, convexity and the l-index boundedness of the functions α(z) and β(z), such that α(z^4) and zβ(z^4) are linear independent solutions of the Weber equation w''-(z^24- u-12) w=0 if u=-12 are investigated.